Changes in milk composition in obese rats consuming a high-fat diet. Issue 3 (26th November 2015) - Bautista, C. J.; Montaño, S.; Ramirez, V.; Morales, A.; Nathanielsz, P. W.; Bobadilla, N. A.; Zambrano, E.
Abstract: Maternal obesity programmes offspring development. We addressed maternal obesity effects induced by high-fat diets on maternal mammary gland (MG) structure and function and offspring brain, liver and fat outcomes. Mothers were fed control (C, n 5) or obesogenic (MO, n 5) diet from the time they were weaned through pregnancy beginning at 120 d, through lactation. At offspring postnatal day (PND) 20, milk leptin and nutrients were determined. At the end of lactation, maternal liver and MG fatty acid profile were measured. Desaturase (Δ6D and Δ5D) and elongase (ELOVL 5 and ELOVL 2) protein was measured by immunohistochemistry and Western blotting (WB) in the liver and WB in the MG. In mothers, liver, MG and milk fat content were higher in MO than in C. Liver arachidonic acid (AA) and EPA and MG EPA were lower in MO than in C. Liver desaturases were higher in MO. The MG was heavier in MO than in C, with decreased Δ5D expression in MO. Desaturases and elongases were immunolocalised in parenchymal cells of both groups. Milk yield, water, carbohydrate content, EPA and DHA were lower, whereas milk leptin and AA were higher in MO than in C. At PND 21 and 36, brain weight was less and fat depots were greater in MO offspring than in C. MO decreased male absolute brain weight but not female absolute brain weight. In conclusion, maternal obesity induced by an obesogenic diet negatively affects maternal liver and MG function with the production of significant changes in milk composition. Maternal obesity adversely affects offspring metabolism and development.